2004
DOI: 10.1598/rrq.39.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Development of reading skills among preschool and primary school pupils

Abstract: S This study investigated the trajectories of preschool and first‐grade children's development of reading skills, as well as the cognitive and social antecedents of that development. One‐hundred and ninety‐six 5‐ to 6‐year‐old children were tested in October and April of their preschool year and again in the first grade. Data included measures of reading ability and its cognitive and social antecedents, which were analyzed using Simplex and Piecewise Growth Curve Modeling. The results showed that during the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
145
1
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 139 publications
(177 citation statements)
references
References 39 publications
22
145
1
9
Order By: Relevance
“…Because reading in our study was operationalized with reading fluency measures (due to lack of variability in reading accuracy measures in Finnish) and spelling with an accuracy measure, we expected that slow reading would be associated with slow RAN (e.g., de Jong & van der Leij, 2002;Eklund et al, 2013;Georgiou et al, 2011;Landerl et al, 2013;Wimmer et al, 1998) and inaccurate spelling would be associated with phonological problems (e.g., Furnes & Samuelsson, 2011;Landerl & Wimmer, 2008;Mayringer et al, 1998;Moll et al, 2014;Niolaki, Masterson, & Terzopoulos, 2013). Second, letter knowledge in kindergarten has been found to be a key predictor of reading and spelling skills (e.g., Kirby, Parrila, & Pfeiffer, 2003;Leppänen, Niemi, Aunola, & Nurmi, 2004;Lerkkanen, Rasku-Puttonen, Aunola, & Nurmi, 2004;Schatschneider, Fletcher, Francis, Carlson, & Foorman, 2004), and in the present study the role of letter knowledge is for the first time examined with respect to unexpected reading and spelling deficits. We expected it to be deficient in both the unexpected poor readers' and the unexpected poor spellers' groups.…”
Section: The Present Studymentioning
confidence: 62%
“…Because reading in our study was operationalized with reading fluency measures (due to lack of variability in reading accuracy measures in Finnish) and spelling with an accuracy measure, we expected that slow reading would be associated with slow RAN (e.g., de Jong & van der Leij, 2002;Eklund et al, 2013;Georgiou et al, 2011;Landerl et al, 2013;Wimmer et al, 1998) and inaccurate spelling would be associated with phonological problems (e.g., Furnes & Samuelsson, 2011;Landerl & Wimmer, 2008;Mayringer et al, 1998;Moll et al, 2014;Niolaki, Masterson, & Terzopoulos, 2013). Second, letter knowledge in kindergarten has been found to be a key predictor of reading and spelling skills (e.g., Kirby, Parrila, & Pfeiffer, 2003;Leppänen, Niemi, Aunola, & Nurmi, 2004;Lerkkanen, Rasku-Puttonen, Aunola, & Nurmi, 2004;Schatschneider, Fletcher, Francis, Carlson, & Foorman, 2004), and in the present study the role of letter knowledge is for the first time examined with respect to unexpected reading and spelling deficits. We expected it to be deficient in both the unexpected poor readers' and the unexpected poor spellers' groups.…”
Section: The Present Studymentioning
confidence: 62%
“…The developments of these skills have been shown to reveal substantial inter-individual differences over the early school years, as well as high inter-individual stability (Crosnoe et al, 2010;Parrila, Aunola, Kirby, Leskinen, & Nurmi, 2005). For example, Leppänen, Niemi, Aunola, and Nurmi (2004) and Parrila et al (2005) showed high stability in reading performance:…”
Section: Teaching Practices and Academic Outcomesmentioning
confidence: 99%
“…The developments of these skills have been shown to reveal substantial inter-individual differences over the early school years, as well as high inter-individual stability (Crosnoe et al, 2010;Parrila, Aunola, Kirby, Leskinen, & Nurmi, 2005). For example, Leppänen, Niemi, Aunola, and Nurmi (2004) and Parrila et al (2005) showed high stability in reading performance:Children who had manifested a higher level of reading performance in the beginning of Grade 1 also outperformed other children at the end of the school year. Moreover, the results for math skills (Aunola, Leskinen, Lerkkanen, & Nurmi, 2004;Crosnoe et al, 2010) have shown that children who enter school with high level skills continue to perform more highly than children who enter school with lower levels of skills.…”
mentioning
confidence: 99%
“…Uma série de investigadores identificaram, inclusive, um conjunto diversificado de competências que são pré-requisito para a aprendizagem de outras habilidades, como a leitura, a escrita e a aritmética, especialmente, nos anos iniciais de escolaridade, pelo que quando um aluno não as apresenta toda a aprendizagem futura será condicionada, podendo culminar no insucesso escolar (Leppänen, Niemi, Aunola & Nurmi, 2004;Levingston, Neef & Cihon, 2009;Wood, Frank & Wacker, 1998). Doutra parte, na literatura da área, está comprovado que os métodos de ensino individualizados são o método mais eficaz de instrução (Siler & VanLehn, 201, Lake, Davis & Madden, 2011).…”
Section: Introductionunclassified